The Forgotten of the Earth: Female Rural Workers. The Question of Class and Gender - Rodríguez Lezica, Lorena; Carámbula, Matías (Agrociencia Uruguay, 2015)
Most of research studies that have addressed the transformations in the rural labour market within a context of family farming decomposition and growing proletarization, have focused on the analysis around labour flexibility and job instability. It is in the nineties that attention is given to the feminization of the rural labour force as one of the tendencies observed in Latin America. Even though Uruguay is one of the countries in the region characterized by a very early expansion of capitalist relations in agriculture, its knowledge production regarding the situation of the rural proletariat is quite recent. Furthermore, an analysis of rural wage labour from a gender perspective remains scarce. This article aims to contribute to the generation of knowledge around transformations in the rural area through a literature review that identifies the lack of a perspective of analysis that integrates and problematizes both class and gender relations. The need to integrate such a perspective to the analysis of the private, public and political spheres is thus well funded, since gender inequality is expressed at home, at work and in the organization.